Comparative Public Theology and Interreligious Education in the Age of Religious Pluralism - Gaetano Sabetta (Religions)
The post-modern era is characterized by a structural religious pluralism, whereby the public dimension of religion has re-emerged as a prominent feature after the relative obscurity of the modern period. In the context of Christianity, the contribution of religion to the common good has been reflected upon in the extensive and profound field of Public Theology. Since its inception in the 1980s, this vast area of studies has encompassed a wide range of topics, including politics, civil society, economics, social issues, and justice. However, the interreligious dimension of public theology appears to be less developed. This is linked, firstly, to the discovery of the public dimension of neighbouring religions and, secondly, to the clarification of the relationship between this and Christian Public Theology. It is evident that the focus of this discussion is the development of a Comparative Public Theology as Interreligious Public Theology. This is a theology that considers the comparative study of religions in a pluralistic context, with the public aspect as its background. On this basis, the contribution has two main aims. Firstly, to identify the field of interreligious public theology, and secondly to concretise it by exploring the field of education from an interreligious and public perspective, i.e., as a contribution to the common good.